Correction of large jawbone defect in the mouse using immature osteoblast–like cells and a 3D polylactic acid scaffold. Issue 4 (18th August 2022) - Suzuki, Shigeto; Venkataiah, Venkata Suresh; Yahata, Yoshio; Kitagawa, Akira; Inagaki, Masahiko; Njuguna, Mary M; Nozawa, Risako; Kakiuchi, Yusuke; Nakano, Masato; Handa, Keisuke; Yamada, Masahiro; Egusa, Hiroshi; et al.
Abstract: Bone tissue engineering has been developed using a combination of mesenchymal stem cells (MSCs) and calcium phosphate–based scaffolds. However, these complexes cannot regenerate large jawbone defects. To overcome this limitation of MSCs and ceramic scaffolds, a novel bone regeneration technology must be developed using cells possessing high bone forming ability and a scaffold that provides space for vertical bone augmentation. To approach this problem in our study, we developed alveolar bone–derived immature osteoblast–like cells (HAOBs), which have the bone regenerative capacity to correct a large bone defect when used as a grafting material in combination with polylactic acid fibers that organize the 3D structure and increase the strength of the scaffold material (3DPL). HAOB-3DPL constructs could not regenerate bone via xenogeneic transplantation in a micromini pig alveolar bone defect model. However, the autogenic transplantation of mouse calvaria–derived immature osteoblast–like cells (MCOBs) isolated using the identical protocol for HAOBs and mixed with 3DPL scaffolds successfully regenerated the bone in a large jawbone defect mouse model, compared to the 3DPL scaffold alone. Nanoindentation analysis indicated that the regenerated bone had a similar micromechanical strength to native bone. In addition, this MCOB-3DPL regenerated bone possesses osseointegration ability wherein a direct structural connection is established with the titanium implant surface. Hence, a complex formed between a 3DPL scaffold and immature osteoblast–like cells such as MCOBs represents a novel bone tissue engineering approach that enables the formation of vertical bone with the micromechanical properties required to treat large bone defects.